Purification and Characterization of Glutathione S-Transferase from rabbit liver - Abdelrahim A. Hunaiti; Ahmad Al hadidi (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Glutathione S-transferases (GSTs) are essential enzymes involved in the detoxification process in animals. They catalyze the conjugation of the antioxidant glutathione (GSH) to various electrophilic compounds, such as environmental toxins, carcinogens, and metabolic by-products, forming mercapturic acids that are more water-soluble and can be excreted. This process protects cells from oxidative stress and chemical damage, and GSTs are particularly abundant in detoxification organs like the liver, kidneys, and lungs. In addition to detoxification, GSTs regulate cellular processes like signal transduction, apoptosis, and cell proliferation. GSTs were purified from rabbit liver with a 22-fold purification and 78-80% yield. The enzyme activity was assessed using 1-chloro-2,4-dinitrobenzene as a substrate, resulting in a specific activity of 91 µmole/min/mg protein. Gel filtration was performed on a Sephadex G-100 column to reveal the enzyme's native molecular weight of approximately 50,000. Polyacrylamide gel electrophoresis in the presence of sodium dodecyl sulfate (SDS-PAGE) was used to examine the enzyme's subunit composition, and its isoelectric points (pI) were determined using chromatofocusing. The purified GST enzyme from rabbit liver exhibited two distinct subunits with molecular weights of 28,000 and 27,000, and all enzyme activity was associated with a single protein band in native polyacrylamide gel electrophoresis. The enzyme displayed a pH optimum around 6.5 and was minimally affected by heat, with 50% of activity retained after eight days of storage at room temperature. The enzyme showed higher conjugation rates for reduced glutathione with substrates like 1,2-epoxy-3-(nitro phenoxy) propane and ethacrynic acid. Chromatofocusing resolved the GSTs into seven isoenzymes with pI values ranging from 7.96 to 9.6. The primary isoenzymes (pI 8.6) were responsible for more than 94% of the overall activity and consisted of two semi-identical subunits. The study successfully purified and characterized rabbit liver GSTs, revealing their subunit composition, isoelectric points, and substrate specificity. The findings suggest that rabbit liver contains multiple isoenzymes with similar immunological properties, with the primary isoenzymes responsible for most of the enzymatic activity. This purification and characterization offer insights into the enzymatic properties and functional diversity of GSTs in animal tissues.The effect of various inhibitors and the substrate activity of the rabbit liver was tested